Proactive Push Research on Personalized Learning Resources Based on Machine Learning - Wang, Lu (Proceedings of ... IEEE International Conference on Unmanned Systems (Online), 2022)
The personalized learning resource push is to respect learners' interests and preferences, behavioral habits, and other differences, so that improving the speed and accuracy of resource acquisition, enhancing learners' learning interests and efficiency, and finally promoting personalized learning. This article analyzes the role of traditional big data technology and machine learning technology in recommending personalized learning resources in educational assistance systems. It combines the background, significance, and technical means of personalized learning resource push to explore the advantages of personalized learning resource push based on machine learning technology, the problems that need to be solved and development paths in the future. Finally, the study finds that machine learning technology, whose model is more stable, has better performance in personalized learning resource delivery. At the same time, machine learning technology can help develop the field of "Artificial Intelligence + Education" rapidly and efficiently.